Evaluation of Tp-e interval and Tp-e/QTc ratio in crush injury patients - Zortuk, Ökkeş; Bedel, Cihan; Selvi, Fatih; Yavuz, Yavuz Fatih; Korkut, Mustafa (Vojnosanitetski pregled, 2025)
Background/Aim. While the association between systemic findings and arrhythmia in crush syndrome is well established, limited literature addresses the correlation between the peak and the end of the T wave (Tp-e) interval, Tp-e/QT ratio, and Tp-e/corrected QT (QTc) ratio intervals with crush injury. The aim of this study was to evaluate the potential for arrhythmia in crush injury patients by utilizing the Tp-e interval, Tp-e/QT ratio, and Tp-e/QTc ratio. Methods. A retrospective study included 42 patients divided into two groups: a group with crush injuries (n = 23) and a control group (n = 19). Demographic data of patients presented with crush injuries were recorded. These details included their age, gender, vital signs, and comorbidities. Tp-e interval, Tp-e/QT ratio, and Tp-e/QTc ratio were also recorded for comparison between the two patient groups. Results. Parameters derived from the electrocardiogram demonstrated significant differences in Tp-e and Tp-e/QTc values between the group with crush injuries and control group. Tp-e was notably higher in patients with crush injuries in comparison to the control group (94.27 ± 27.90 vs. 73.36 ± 11.25, p = 0.024). Furthermore, it was found that the Tp-e/QTc ratio was markedly elevated among patients with crush injuries compared to the control group (0.223 ± 0.064 vs. 0.180 ± 0.030, p = 0.010). Receiver operating characteristic curve analysis showed that at a Tp-e cut-off value of 79.50, trauma severity could be predicted with 82.6% sensitivity and 73.7% specificity, indicating the prediction capability of Tp-e in trauma severity (area under the curve: 0.805, p < 0.001). Conclusion. In patients presenting to the emergency department with crush injuries, we posit that the Tp-e interval and Tp-e/QTc ratio on electrocardiogram may function as markers for potential arrhythmia progression.